Navigating the Micropolitical Landscape of Higher Education - Jared Rawlings (Academic Chairpersons Conference Proceedings, 2019)
Academic chairpersons experience conflicts with a variety of stakeholders in higher education. The purpose of this session is to present current research about micropolitics in education and discuss strategies for understanding the micropolitical landscape of academia and for attaining micropolitical literacy to navigating conflicts.
Keywords: Micropolitics; Higher Education; Faculty; Support Staff; Conflict Resolution